Fatores críticos relativos à abertura do setor de transporte de petróleo e derivados - Biolchini, Luiz C. A. (2001)
The current evolution process of the Brazilian oil industry inntiated with the New Oil Law Law Nr. 9.478 of August 6Ü1, 1997 and the domestic market opening expected for 2001, will bring some changes in the national petroleum chain. These modifícations shall come as result of the competition increase both from new players comming into this sector and by the dispute between the domestic products against the imported ones as well, shaping new competitive scenario in the petroleum products market. Therefore, import and export of oil and productus by new players in association with their transportation and the use of the existent storage and transport infra-structure are issues that must be analysed through the regulations point of view. Within this ongoing process, the levei of regulation is essential once legal markets structured for competition demand set of preestablished rules and completely deregulated economies may create heavy disparities to society. The purpose of this dissertation is to analyse the main criticai administrative and economic factors in the petroleum and produtcts transportation sector, which shall be considered in the opening of this activity to new players, in order to achieve an effective Vil transition into market oriented economy, within the new model of the State acting as Regulator. It is an explanatory research as indicates the criticai factors and also exploratory since it regards fíeld offering little knowledge and available experience in Brazil, as well as documentary and bibliographical study, since it is based on laws, decrees, ordinances, documentation of public institutions, books, articles etc. The investigation process consist on the search of the historical evolution of this sector until nowadays, the study of the current applicable regulation, the fundamentais of the regulation theory and the international experience, description of the current domestic petroleum and products transportation sector focusing in the maritime and pipeline transportation, while making criticai analysis of the sector based on the Law Nr.9.478/97 and the market opening. The study identifies criticai factors which allow the conditions for competition oriented market, i.e. supply, demand, service accessibility by the society, quality and safety, price information, usage of products and services and proper State control. These factors are associated with information access, tariffs regulation, the control of entry and exit, rendered services quality control and the introduction of tansition period from a controlled system to competive maket.